Imaging predictors of incident heart failure: a systematic review and meta-analysis. Issue 5 (May 2021) - Georgiopoulos, Georgios; Aimo, Alberto; Barison, Andrea; Magkas, Nikolaos; Emdin, Michele; Masci, Pier-Giorgio
Abstract : Background: Preventing the evolution of subclinical cardiac disease into overt heart failure is of paramount importance. Imaging techniques, particularly transthoracic echocardiography (TTE), are well suited to identify abnormalities in cardiac structure and function that precede the development of heart failure. Methods: This meta-analysis provides a comprehensive evaluation of 32 studies from 11 individual cohorts, which assessed cardiac indices from TTE (63%), cardiovascular magnetic resonance (CMR; 34%) or cardiac computed tomography (CCT; 16%). Eligible studies focused on measures of left ventricular geometry and function and were highly heterogeneous. Results: Among the variables that could be assessed through a meta-analytic approach, left ventricular systolic dysfunction, defined as left ventricular ejection fraction (LVEF) lower than 50%, and left ventricular dilation were associated with a five-fold [hazard ratio (HR) 4.76, 95% confidence interval (95% CI) 1.85–12.26] and three-fold (HR 3.14, 95% CI 1.37 –7.19) increased risk of heart failure development, respectively. Any degree of diastolic dysfunction conveyed an independent, albeit weaker, association with heart failure (HR 1.48, 95% CI 1.11–1.96), although there was only a trend for left ventricular hypertrophy in predicting incident heart failure (hazard ratio 2.85, 95% CI 0.82–9.85). Conclusion: LVEF less than 50%, left ventricular dilation and diastolic dysfunction are independent predictors of incident heart failure among asymptomatic individuals, while left ventricular hypertrophy seems less predictive. These findings may serve as a framework for implementing imaging-based screening strategies in patients at risk of heart failure and inform future studies testing preventive or therapeutic approaches aiming at thwarting or halting the progression from asymptomatic (preclinical) to overt heart failure. Abstract : Supplemental Digital Content is available in the text